Manajemen Sarana dan Prasarana Pendidikan - Mukhroji Mukhroji (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2018)
Abstract: The facility is a direct means to reach a goal. And infrastructure is an indirect means to reach a goal. Educational facilities and infrastructure management is the control and utilization of all the factors and resources either directly or indirectly with the planning necessary to achieve educational goals. With the good management of facilities and infrastructure, each institution can improve the quality of education with a reliable output. And the use of appropriate facilities and infrastructure can make an institution successful and still exist in today’s era of globalization Key words: Management, Facilities - Infrastructure, and Quality of Education.